Toward a mechanistic understanding of larval dispersal: insights from genomic fingerprinting of the deep‐sea hydrothermal vent tubeworm Riftia pachyptila - Timothy M. Shank; Kenneth M. Halanych (Marine Ecology, 2007)
Larval dispersal is critical for the maintenance of species populations in patchy and ephemeral hydrothermal vent habitats. On fast‐spreading ridges, such as the East Pacific Rise, rates of habitat turnover are comparable to estimated lifespans of many of the inhabiting species. Traditionally, dispersal questions have been addressed with two very different approaches, larval studies and population genetics. Population genetic studies of vent‐endemic species have been informative for determining whether patterns of dispersal are suggestive of stepping stone or island models and estimating rates of gene flow (effective migrants per generation) over broad geographic ranges. However, these studies leave fundamental questions unanswered about the specific mechanisms by which larvae disperse and species maintain their populations and biogeographic ranges. With the goal of examining genetic structure and elucidating alternative larval dispersal mechanisms, we employed a genomic DNA fingerprinting technique, amplified fragment length polymorphisms (AFLPs). To assess the potential utility of AFLPs, and genetic structure of the hydrothermal vent tubeworm Riftia pachyptila , genomic ‘fingerprints’ were recovered from 29 individuals from five vent fields spanning a distance of up to c. 5000 km along the East Pacific Rise. In contrast to previous population genetic studies that found little to no genetic structure using allozymes and mitochondrial DNA, genetic analyses of 630 polymorphic AFLP loci identified distinct subclades within R. pachyptila populations. Significant levels of differentiation were observed among populations from all vent regions as well as within each region. Discrete assemblages of tubeworms separated by as little as c. 400 m within a given vent region were genetically distinguishable and cohorts (based on size‐frequency distribution) within an aggregation were found to be most closely related. These results suggest that mechanisms of larval dispersal act to retain cohort fidelity in R. pachyptila .